Lay Understandings of the Structure of Intimate Partner Violence in Relationships: An Analysis of Behavioral Clustering Patterns - Minto, Kiara (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is common and has a lasting negative impact on the health and well-being of victims and survivors. People?s mental frameworks (schemas) of IPV are central in allowing them to identify and respond to IPV. Early recognition of IPV is essential to reducing the cumulative harm caused by repeated instances of abusive behaviors. In relationships with IPV, abuse typically starts with relatively less harmful behaviors, which may be ambiguous in isolation, and escalates. The present research examines the content of lay people?s IPV schemas to gain insight into their understanding of the presentation and progression of IPV. Participants (N = 168) were presented with two exemplars each of three different relationship types (nonabusive, nonphysically abusive, and physically abusive) resulting in a total of six exemplars. They were also presented with a list of behaviors that comprised nonabusive, nonphysically abusive, and physically abusive actions. For each exemplar, participants selected the behaviors they considered most likely to co-occur with the exemplar behavior. They then rated the abusiveness of the behavioral clusters they had created. Results indicate that participants distinguish nonabusive, physically abusive, and nonphysically abusive clusters. Nonphysically abusive behavior clusters are seen as less abusive than physically abusive behavior clusters, with nonphysically abusive behaviors more likely to be grouped with nonabusive behaviors.